Nutrients in Infancy - Mi Kyung Lee (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
Infants are not just small adults; they have a complex set of nutrient requirements and interactions to account for the high metabolic rate, growth, immunological and cognitive development, etc. Each year there are 138 million births, including 30 million from the least developed countries, where health is most at risk. Nutrition during infancy establishes growth patterns and development which moderate short term and long term health and life expectancy. There is continuing progress in understanding the nutrient composition of breastmilk and the importance nutritious and timely complementary foods. Nutrients at particular risk in the first years of life are iron, iodine, and vitamins A and D. There are still gaps in our knowledge on the influence of maternal diet, body composition and nutritional status on breastmilk nutrients. Interaction of nutrients with the human microbiome and gastro-intestinal tract hormonal secretion are developing fields. While breastmilk remains the "gold standard of pediatric nutrition", the provisions of nutrients providing for optimal health in infant formulae, including nutrients and probiotics remains an area of research. The assessment of body composition for research and clinical practice has progressed rapidly and is important in understanding later obesity. After six months of age, there are new issues of the interaction of weaning foods and later family foods with the maturing gastro-intestinal tract to promote health and growth. Infant nutrition is made more difficult (and interesting) by the many cultural beliefs related to feeding practices. Developments in all of these fields of research into pediatric nutrition will be explored in this special issue together with state of the art reviews.